UiTM as a world-class university: prospects and challenges / Shafi Mohamad - Mohamad, Shafi (Universiti Teknologi MARA, Sarawak, 2006)
Vision 2020 as articulated by the government aims to make Malaysia a fully developed nation by 2020. A critical part of the strategy towards realizing this objective includes the creation of a highly skilled workforce. Amongst the traits possessed by the workforce of the industrialized nations include knowledge, creativity, innovativeness and mobility, besides their readiness to face the challenges posed by the twin threats of, globalization and the knowledge economy. UiTM, in its capacity' as the largest public, university in Malaysia, has an important role to play towards achieving the objectives, of Vision 2020. Therefore, the mission of UiTM to become a worldclass university is in tandem with the objectives of Vision 2020. This paper therefore briefly outlines some of the prospects and challenges likely to be encountered on the journey towards attaining the status of a world-class university.